2016
DOI: 10.3390/ph9030048
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Improvement Increases the Protective Activity of Broccoli Sprout Juice in a Human Intestinal Cell Model of Gut Inflammation

Abstract: Benefits to health from a high consumption of fruits and vegetables are well established and have been attributed to bioactive secondary metabolites present in edible plants. However, the effects of specific health-related phytochemicals within a complex food matrix are difficult to assess. In an attempt to address this problem, we have used elicitation to improve the nutraceutical content of seedlings of Brassica oleracea grown under controlled conditions. Analysis, by LC-MS, of the glucosinolate, isothiocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 84 publications
1
18
0
Order By: Relevance
“…Exogenous elicitation with yeast extracts of Saccharomyces cerevisiae (0.1% w / v ) had little or no significant influence on total phenolic content and antioxidant activity of sprouted wheat [ 25 ], while significantly increased the levels of ferulic, p-coumaric and syringic acids in broccoli sprouts [ 178 ]. Other investigated biotic elicitors include mannitol [ 179 ], sucrose [ 180 , 181 , 182 ], glucose [ 180 , 181 , 183 ], glucosamine and collagen [ 184 ] as well as tea tree [ 175 ] and Salix daphnoides bark [ 25 ] extracts. Moreover, among protein elicitors, fish protein hydrolysates (FPH)—produced from byproduct of fishery industry—seem interesting due to their high content of proline and proline precursors.…”
Section: Factors Influencing Nutritional Quality Of Germinated Whomentioning
confidence: 99%
“…Exogenous elicitation with yeast extracts of Saccharomyces cerevisiae (0.1% w / v ) had little or no significant influence on total phenolic content and antioxidant activity of sprouted wheat [ 25 ], while significantly increased the levels of ferulic, p-coumaric and syringic acids in broccoli sprouts [ 178 ]. Other investigated biotic elicitors include mannitol [ 179 ], sucrose [ 180 , 181 , 182 ], glucose [ 180 , 181 , 183 ], glucosamine and collagen [ 184 ] as well as tea tree [ 175 ] and Salix daphnoides bark [ 25 ] extracts. Moreover, among protein elicitors, fish protein hydrolysates (FPH)—produced from byproduct of fishery industry—seem interesting due to their high content of proline and proline precursors.…”
Section: Factors Influencing Nutritional Quality Of Germinated Whomentioning
confidence: 99%
“…The anti-inflammatory mechanisms of broccoli sprouts are probably associated with the nuclear factor-kappa B (NF-κB) and nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathways [27]. Both in vitro and in vivo experiments, as well as clinical trials, mainly exhibit anti-inflammatory effects of broccoli sprouts, which showed high concentrations of sulforaphane and a group of phenolic compounds, including anthocyanins, isoquercetin, chlorogenic and cinnamic acids, via inhibiting inflammatory mediators such as a nitric oxide (NO), decreasing the levels of proinflammatory cytokines such as tumor necrosis factor α (TNF-α), interleukin-6 (IL-6), and IL-1β, and increasing the levels of anti-inflammatory cytokines such as IL-10 and IL-22 [27,28,55,72,113,114]. For example, a study showed that sulforaphane-enriched broccoli sprouts inhibited activation of the NF-κB signaling pathway and the secretions of inflammatory proteins (inducible nitric oxide synthase (iNOS), cyclooxygenase 2 (COX-2), TNF-α, IL-6, IL-1β, and prostaglandin E2 (PGE2)) in microglial cells (BV2) and male ICR (Institute of Cancer Research) mice.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Within this context, sprouts provide the opportunity for implementing quick, flexible, and versatile procedures to concurrently develop metabolic variants for subsequent characterizations, comparisons to controls, and application of multivariate statistical analyses to discriminate the chemical entities exercising an active role on observed biological effects. By way of example, this rationale was applied by Ferruzza et al [227] to show a protective effect by Brassica oleracea sprouts against a human model of gut inflammation developed in Caco-2 cells.…”
Section: Sprouts and Human Health: Rewards And Riddlesmentioning
confidence: 99%